Periodic health checkups reduce the risk of hospitalization in patients with type 2 diabetes - Hamasaki, Hidetaka; Yanai, Hidekatsu (Frontiers in Clinical Diabetes and Healthcare, 2023)
Introduction Periodic health checkups (PHCs) represent a unique system in Japan that is useful for the early detection of lifestyle-related diseases and cardiovascular diseases (CVDs). This study aims to investigate the association of PHCs with the hospitalization risk of patients with type 2 diabetes mellitus (T2DM). Methods A retrospective cohort study was conducted from April 2013 to December 2015 and included participant information such as CVD history, lifestyle, and whether PHC was conducted in addition to regular medical examinations. Difference in clinical data between patients with and without PHC was examined. Furthermore, Cox regression analysis was performed to investigate the independent association of PHCs with hospitalization. Results Herein, 1,256 patients were selected and followed up for 2.35 ± 0.73 years. In the PHC group, body mass index, waist circumference, proportion of patients with a history of CVD, and number of hospitalizations were lower than those in the non-PHC group. Furthermore, the PHC group exhibited a significant association with lower hospitalization risk (hazard ratio = 0.825; 95% confidence interval, 0.684 to 0.997; p = 0.046) in the Cox model. Conclusion This study revealed that PHCs minimized the risk of hospitalization in patients with T2DM. Furthermore, we discussed the effectiveness of PHCs in enhancing health outcomes and reducing health care costs in such patients.